Highly impulsive rats: modelling an endophenotype to determine the neurobiological, genetic and environmental mechanisms of addiction - Bianca Jupp; Daniele Caprioli; Jeffrey W. Dalley (The Company of Biologists, 2013)
Impulsivity describes the tendency of an individual to act prematurely without foresight and is associated with a number of neuropsychiatric co-morbidities, including drug addiction. As such, there is increasing interest in the neurobiological mechanisms of impulsivity, as well as the genetic and environmental influences that govern the expression of this behaviour. Tests used on rodent models of impulsivity share strong parallels with tasks used to assess this trait in humans, and studies in both suggest a crucial role of monoaminergic corticostriatal systems in the expression of this behavioural trait. Furthermore, rodent models have enabled investigation of the causal relationship between drug abuse and impulsivity. Here, we review the use of rodent models of impulsivity for investigating the mechanisms involved in this trait, and how these mechanisms could contribute to the pathogenesis of addiction.